2005
DOI: 10.1051/0004-6361:20052684
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the optical counterparts of high-mass X-ray binaries through optical photometry and spectroscopy

Abstract: Abstract. We present the results of our search for optical counterparts to high-mass X-ray transient sources discovered by various X-ray missions. We obtained CCD images of the X-ray fields through BVR and Hα filters to identify early-type stars in the R − Hα versus B − V colour-colour diagram. We also obtained medium-resolution spectroscopy of the candidates in order to confirm the presence of Hα emission and perform spectral classification. We report on the discovery of the optical counterparts to two X-ray … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
88
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(96 citation statements)
references
References 36 publications
(48 reference statements)
8
88
0
Order By: Relevance
“…, 2004). Studying the nature of the source Reig et al (2005b) found that the optical counterpart is neither a Be star nor a supergiant star (the most adequate classification was to be B0.5 II-III at the distance of ∼ 3 kpc) and so IGR J00370+6122 appears difficult to fit within the classical classification scheme of HMXBs (see, however, González-Galán et al 2014 for the recent classification of the source as a BN0.7Ib and discussion its possible supergiant nature). Later den Hartog et al (2006) and in't Zand et al (2007) showed that the source is a recurrent transient X-ray pulsar (with a spin period of P spin ≃ 359 s) in an eccentric orbit (with the orbital period P orb = 15.667 days), demonstrating s flaring behavior within a dynamic range about 10-20.…”
Section: Discussionmentioning
confidence: 99%
“…, 2004). Studying the nature of the source Reig et al (2005b) found that the optical counterpart is neither a Be star nor a supergiant star (the most adequate classification was to be B0.5 II-III at the distance of ∼ 3 kpc) and so IGR J00370+6122 appears difficult to fit within the classical classification scheme of HMXBs (see, however, González-Galán et al 2014 for the recent classification of the source as a BN0.7Ib and discussion its possible supergiant nature). Later den Hartog et al (2006) and in't Zand et al (2007) showed that the source is a recurrent transient X-ray pulsar (with a spin period of P spin ≃ 359 s) in an eccentric orbit (with the orbital period P orb = 15.667 days), demonstrating s flaring behavior within a dynamic range about 10-20.…”
Section: Discussionmentioning
confidence: 99%
“…The instrumental magnitudes were used to construct a colour-colour (R−Hα vs. B−V) diagram following the procedure described in Reig et al (2005). Be stars are expected to occupy the upper (because they are Hα emitters) and left (because they are early-type objects).…”
Section: Optical Observations and Infrared Datamentioning
confidence: 99%
“…7), occasionally interrupted by short spindown intervals (e.g. middle panel of Photometric and spectroscopic observations performed in 2004 (Reig et al 2005) during the faint state showed that SAX J2103.5+4545 continued to emit X-rays even after having completely lost the Be disc. A gradual flux decline was also seen during quiescence after the type II outburst in 2004, but the frequency continued to increase (see Fig 7).…”
Section: X-ray Behaviourmentioning
confidence: 99%